Analisis Akuntabilitas Keuangan dan Pendayaguaan Dana Zakat, Infaq dan Shadaqah pada Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah Kota Medan (International Forum of Researchers and Lecturers, 2023)
This study aims to analyze financial accountability and utilization of zakat, infaq and shadaqah funds at Lazismu Medan City. This study uses qualitative research using primary data and secondary data approaches. Data collection techniques were carried out by interviews, observation and documentation. To motivate muzakki to pay ZIS through the Zakat Management Organization (OP Z), it is necessary to increase the credibility of OPZ by applying accountability values, namely trustworthiness, professionalism and transparency. The results of the study show that financial accountability in the Amil Zakat, Infaq and Shadaqoh Muhammadiyah Institutions in Medan City has been proven to have implemented PSAK 109 as the accounting standard used. Aspects of presenting ZIS at Lazismu are implemented by preparing financial reports consisting of statements of financial position, cash flow reports, reports on changes in funds, reports on changes in assets under management and notes to financial statements (CALK). Financial reports on the management of ZIS are published once a year. Apart from that, Lazismu also performs regular monthly reporting. And Utilization and ZIS at Lazsimu Medan City experienced an increase in distribution in 2021 more ZIS funds were distributed and programs were implemented compared to 2020. This shows that more mustahiq receive benefits from zakat, infaq and shadqah funds.